Co-N-C electrocatalyst with nanoflower structure as well as preparation method and application of Co-N-C electrocatalyst

By adopting Co-N-C electrocatalyst with nanoflower structure, the problem of low activity of existing three-functional electrocatalysts is solved, and an efficient three-functional electrocatalyst is achieved, which significantly improves energy conversion efficiency and simplifies the preparation process, which is suitable for electrolytic water and rechargeable zinc-air batteries.

CN119144989APending Publication Date: 2024-12-17DEZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411629005.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing trifunctional electrocatalysts have low activity, especially non-precious metal-based trifunctional electrocatalysts. The precious metal-based trifunctional electrocatalysts have high cost, making it difficult to develop efficient, stable and low-cost electrocatalysts to achieve oxygen reduction, oxygen evolution and hydrogen evolution reactions.

Method used

The Co-N-C electrocatalyst with nanoflower structure is prepared by SBA-15 as a template, and is calcined to achieve the efficient three-functionality of the Co-N-C electrocatalyst, and can simultaneously perform electrochemical hydrogen evolution reaction, oxygen evolution reaction and oxygen reduction reaction. .

Benefits of technology

It significantly improves energy conversion efficiency, provides more active sites and better mass transfer characteristics, simplifies the preparation process, facilitates industrial production, reduces the activation energy of the reaction, and improves catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144989A_ABST
    Figure CN119144989A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy conversion and storage, in particular to a preparation method and application of a Co-N-C electrocatalyst with a nanoflower structure. The electrocatalyst has a nanoflower structure. The Co-N-C electrocatalyst is prepared through calcination by using SBA-15 as a template, and the Co-N-C electrocatalyst is a three-function catalyst and can be used for an electrochemical hydrogen evolution reaction HER, an oxygen evolution reaction OER and an oxygen reduction reaction ORR at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy conversion and storage, and in particular to a Co-NC electrocatalyst with a nanoflower structure, a preparation method and an application thereof. Background Art

[0002] With the continuous growth of global energy demand and the increasingly severe environmental problems, the development of efficient, stable and low-cost electrocatalysts has become the key to achieving renewable energy conversion and storage. In new energy devices such as rechargeable zinc-air batteries, water electrolysis, and fuel cells, the three reactions of oxygen reduction (ORR), oxygen evolution (OER) and hydrogen evolution (HER) play a very important role. Among them, ORR and OER are two key reactions in rechargeable zinc-air batteries, while OER and HER are the core reactions in water electrolysis. Since these three reactions all involve multi-electron transfer, their slow kinetics lead to large overpotentials required for the reaction. In practical device applications, the cathode of the rechargeable zinc-air battery needs to switch back and forth between ORR and OER during the charge and discharge process, so ORR / OER bifunctional electrocatalysts are needed; while in water electrolysis devices, the use of OER / HER bifunctional electrocatalysts can reduce costs. Therefore, the development of ORR, OER and HER trifunctional electrocatalysts is of great significance for the application of rechargeable zinc-air batteries and water electrolysis.

[0003] The research and development and application of high-performance electrocatalysts are considered to be a crucial link. ORR is a key reaction on the cathode of zinc-air batteries, which involves steps such as adsorption, dissociation, electron transfer and product desorption of oxygen on the catalyst surface. In order to accelerate this process, it is necessary to develop efficient catalysts to reduce the activation energy barrier of the reaction and increase the reaction rate. The electrochemical water splitting reaction, which is the decomposition of water molecules into hydrogen and oxygen under the action of an electric field, is a reaction involving complex electrochemical processes, and its efficiency and energy consumption are directly affected by the performance of the electrocatalyst. High-performance electrocatalysts significantly reduce the activation energy of the reaction by providing an efficient reaction interface, accelerate the process of water molecules dissociating into hydrogen ions and oxygen ions, thereby increasing the rate of hydrogen production while greatly reducing energy consumption. Therefore, the development of electrocatalysts with high activity, high stability and low cost is a hot spot and difficulty in the current scientific research field.

[0004] With the rapid development of nanotechnology, surface science and computational materials science, new avenues have been opened up for the design and preparation of high-performance electrocatalysts. For example, by finely regulating the nanostructure of the catalyst, introducing specific functional groups or constructing a heterojunction structure, the catalytic activity and selectivity of the catalyst can be significantly improved. In addition, the exploration of new catalytic materials, such as non-precious metal-based catalysts, two-dimensional materials, MOFs (metal organic frameworks), etc., also provides the possibility for the economical and scalable application of electrocatalysts.

[0005] The trifunctional electrocatalysts reported in the prior art include non-precious metal and precious metal-based catalysts. There are very few non-precious metal-based trifunctional electrocatalysts, and the reported non-precious metal-based trifunctional electrocatalysts are still lacking in activity and stability. The currently reported precious metal-based trifunctional electrocatalysts are mainly based on PtCo / Ir, RhCu and other systems, which are very expensive. The Ru-based system has the advantage of low cost compared to the Pt / Pd / Ir / Rh system, but the performance of the Ru-based system as a trifunctional electrocatalyst is still very limited, so finding and developing new trifunctional catalysts is still a very difficult task. Summary of the invention

[0006] In view of the problem of low activity of trifunctional catalysts in the prior art, the present invention provides a Co-NC electrocatalyst with a nanoflower structure and a preparation method and application thereof, wherein the Co-NC electrocatalyst is a highly efficient trifunctional electrocatalyst. The electrocatalyst can simultaneously realize electrochemical hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), significantly improving energy conversion efficiency.

[0007] The present invention is achieved through the following technical solutions: A Co-NC electrocatalyst has a nanoflower structure and is prepared by calcining using SBA-15 as a template.

[0008] The preparation method of the Co-NC electrocatalyst comprises the following steps: S1. Weigh SBA-15 and cobalt nitrate and dissolve them in ethanol. Use potassium hydroxide to adjust the pH value of the solution to 8. Evaporate the solution to dryness at 60°C. S2. The evaporated sample is calcined at high temperature in a tube furnace to obtain a Co-NC electrocatalyst.

[0009] Furthermore, the mass ratio of the SBA-15 to cobalt nitrate is 1:3.

[0010] The amount of ethanol added was limited to 0.5 g SBA-15 per 30 mL ethanol.

[0011] Furthermore, the high temperature calcination temperature is 600-800°C.

[0012] Furthermore, the preparation method of SBA-15 comprises the following steps: Weigh 6.0g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) and dissolve it in water. Use hydrochloric acid to adjust the pH of the solution and keep it at 40℃ for 3h. Then add TEOS (tetraethoxysilane), stir for 24h, and age it for 24h. After filtering, washing and drying, calcinate it in a muffle furnace at 550℃ for 8h to obtain the final sample SBA-15.

[0013] The present invention also provides the use of the Co-NC electrocatalyst in electrochemical hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR).

[0014] Compared with the prior art, the beneficial technical effects of the present invention are as follows: (1) The Co-NC electrocatalyst prepared in the present application has a nanoflower structure, which provides more active sites and better mass transfer properties, thereby improving the electrocatalytic performance of the material.

[0015] (2) The Co-NC electrocatalyst synthesis method has simple steps and only requires hydrothermal reaction and calcination, which can be easily realized in industrial production.

[0016] (3) The Co-NC electrocatalyst is a trifunctional electrocatalyst that can be used simultaneously for the HER and OER reactions in the water electrolysis reaction and the oxygen reduction reaction (ORR). Currently, no Co-NC electrocatalyst has been found to be suitable for the trifunctional catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the XRD pattern of the Co(OH)2 material prepared before calcination in Example 1.

[0018] Figure 2 is the XRD pattern of Co-NC prepared in Example 1.

[0019] Figure 3 It is the SEM picture of SBA-15.

[0020] Figure 4 This is a SEM image of the 600°C-Co-NC prepared in Example 1 of the present invention.

[0021] Figure 5 This is a SEM image of the 700°C-Co-NC prepared in Example 2 of the present invention.

[0022] Figure 6 This is the SEM image of the 750°C-Co-NC prepared in Example 3 of the present invention.

[0023] Figure 7This is a SEM image of 800°C-Co-NC prepared in Example 4 of the present invention.

[0024] Figure 8 This is a SEM image of Co-NC prepared in Comparative Example 1 of the present invention without adding a template.

[0025] Fig. 9 is a graph of the specific surface area of ​​Co-NC prepared in Examples 1-4 of the present invention; Fig.10 3 is a LSV curve diagram of the ORR of Co-NC prepared in Examples 1-4 of the present invention.

[0026] Fig.11 It is an OERLSV curve diagram of the Co-NC material with a nanoflower structure at 750° C. prepared in Example 3 of the present invention.

[0027] Fig.12 It is an OERLSV curve diagram of the Co-NC material with a granular structure prepared in Comparative Example 1 of the present invention at 750°C.

[0028] Fig.13 3 is the LSV curve of HER of Co-NC prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0029] The present invention will be further described below by way of examples, the purpose of which is to provide a better understanding of the present invention.

[0030] Example 1 S1. Weigh 6.0g P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) and dissolve it in water. Use hydrochloric acid to adjust the pH of the solution and keep it at 40℃ for 3h. Then add TEOS (tetraethoxysilane), stir for 24h, and then age for 24h. After filtering, washing and drying, finally calcine in a muffle furnace at 550℃ for 8h to obtain the final sample SBA-15.

[0031] S2. Weigh 0.50 g SBA-15 and 1.65 g cobalt nitrate and dissolve them in 30 mL ethanol. Use potassium hydroxide to adjust the solution pH to 8. Evaporate the solution at 60 °C.

[0032] S3. The evaporated sample obtained in S2 is calcined in a tube furnace at a high temperature of 600° C., and then the template is removed by using an acid or an alkali to obtain Co-NC with a nanoflower structure.

[0033] Example 2 The difference between Example 2 and Example 1 is that the calcination temperature is 700° C., and the other conditions are exactly the same.

[0034] Example 3 The difference between Example 3 and Example 1 is that the calcination temperature is 750° C., and the other conditions are exactly the same.

[0035] Example 4 The difference between Example 4 and Example 1 is that the calcination temperature is 800° C., and the other conditions are exactly the same.

[0036] Comparative Example 1 S1. Weigh 1.65 g of cobalt nitrate and dissolve it in 30 mL of ethanol, and adjust the pH of the solution to 8 with potassium hydroxide. Evaporate the solution to dryness at 60°C.

[0037] S2. The sample obtained in S1 is calcined at high temperature in a tube furnace to obtain Co-NC with a particle structure.

[0038] Characterization of materials: Figure 1 This is the XRD data of the Co(OH)2 material prepared before calcination in Example 1. The Co(OH)2 material has diffraction peaks at 19.3°, 32.5°, 38.0°, 51.2°, 58.1° and 61.8°, which are consistent with the PDF card, indicating that the Co(OH)2 catalyst material was successfully prepared.

[0039] Figure 2 This is the XRD data of the Co-NC catalyst material prepared in Example 1. The XRD peak of Co-NC has a standard C signal peak at 26.2°, confirming that the electrocatalyst is a Co-NC material.

[0040] Figure 3 This is the SEM image of SBA-15 prepared in step 1 of Example 1. Figure 4 This is the SEM image of the 600°C-Co-NC prepared in Example 1. From the image, it can be seen that the morphology of the material has wrinkles and protrusions of nanosheet structure on the surface. Figure 5 This is the SEM image of the 700℃-Co-NC prepared in Example 2. From the image, it can be seen that the wrinkled surface of the material gradually turns into a thin layer of nanoflowers. Figure 6 It shows the SEM image of 750℃-Co-NC prepared in Example 3. It can be seen from the image that the wrinkled surface of the material has been completely transformed into a thin layer of nanoflowers. Figure 7 This is the SEM image of the 800°C-Co-NC prepared in Example 4. It can be seen from the image that the morphology of the thin layer of nanoflowers of the material is gradually destroyed.

[0041] Figure 8This is a SEM image of Co-NC prepared in Comparative Example 1, from which it can be seen that the morphology of the material is composed of nanoparticles, indicating that when SBA-15 is not added, the obtained Co-NC is in granular form.

[0042] Fig. 9 The specific surface area of ​​Co-NC prepared in Examples 1-4 at 600°C, 700°C, 750°C, and 800°C is shown. It can be seen from the figure that the specific surface area at 600°C, 700°C, and 750°C decreases with the increase of temperature, and is the lowest at 800°C, indicating that high temperature not only destroys the structure of the nanoflower.

[0043] Performance Testing (1) Configuration of electrode materials: 3.0 mg of the Co-NC catalyst prepared in Examples 1-4 and Comparative Example 1 was dispersed in 300 μl of a mixed solution of isopropanol and water (volume ratio 1:1), 2 drops of Nafion ion polymer were added to the mixed solution, and the mixed solution was ultrasonicated for 15-20 min to obtain a uniform ink.

[0044] (2) Prepare water electrolysis electrodes and electrolytes: Prepare 0.1 mol / L potassium hydroxide solution (for hydrogen evolution reaction HER at the cathode) and 0.5 MH2SO4 solution (for oxygen evolution reaction OER at the anode), and then measure 250 mL of electrolyte into a beaker as the electrolyte for the next test. The catalyst material prepared in step 1 is evenly dropped onto the platinum carbon electrode and connected to the rotating disk electrode as the working electrode, the Ag / AgCl electrode as the reference electrode, and the graphite rod as the counter electrode, which is connected to the electrochemical workstation.

[0045] (3) Prepare the ORR reaction electrode and electrolyte: Prepare 0.1 mol / L potassium hydroxide solution, and then measure 250 mL of potassium hydroxide solution and pour it into a beaker as the electrolyte for the following test. The catalyst material prepared in step 1 is evenly dropped onto the platinum carbon electrode and connected to the rotating disk as the working electrode, the Ag / AgCl electrode as the reference electrode, and the graphite rod as the counter electrode, which is connected to the electrochemical workstation.

[0046] (4) After confirming that all parameters are set correctly, start the experiment. The electrochemical workstation is controlled to perform potential scanning or apply current according to the set parameters, and the response current of the electrode system is recorded in real time. Each set of data should be tested multiple times until the data is stable. The results are as follows: Figure 10-13 shown.

[0047] Fig.10The LSV curves of the ORR of Co-NC prepared in Examples 1-4 at 600°C, 700°C, 750°C, and 800°C are shown in Figure 1. It can be seen from the figure that the half-wave potential and initial potential of the electrocatalyst material prepared in Example 3 are both the largest, indicating that its performance is optimal.

[0048] Fig.11 This is the LSV curve of the OER of the nanoflower structure Co-NC prepared in Example 3 at 750°C. It can be seen from the figure that the OER performance of the material at 750°C is: the current density is 10mA / cm 2 , 1.68V, that is, the OER crossing point is 420mV.

[0049] Fig.12 This is the LSV curve of the OER of the particle structure Co-NC prepared in Example 1 at 750°C. From the figure, it can be seen that the OER performance of the material is: the current density is 10mA / cm 2 , 1.76V, that is, the OER crossing point is 530mV.

[0050] By comparison, it can be seen that the Co-NC material with nanoflower structure exhibits a lower overpotential in OER than the Co-NC material with particle structure. This indicates that the material with nanoflower structure is more effective in electrocatalytic OER and requires a lower potential to achieve the same current density. The reason is that the nanoflower structure provides more active sites and better mass transfer properties.

[0051] Fig.13 The LSV curves of HER of Co-NC prepared in Examples 1-4 at 600°C, 700°C, 750°C, and 800°C. It can be seen from the figure that the HER performance of the material at 750°C is: when the current density is 10mA / cm2, -0.60V, that is, the HER transition point is 60mV.

Claims

1. A Co-NC electrocatalyst, characterized in that: The electrocatalyst has a nanoflower structure; The Co-NC electrocatalyst is prepared by calcination using SBA-15 as a template.

2. A method for preparing the Co-NC electrocatalyst according to claim 1, characterized in that: The steps include: S1. Weigh SBA-15 and cobalt nitrate and dissolve them in ethanol. Use potassium hydroxide to adjust the pH value of the solution to 8. Evaporate the solution to dryness at 60°C. S2. The evaporated sample is calcined at high temperature in a tube furnace to obtain a Co-NC electrocatalyst.

3. The method for preparing the Co-NC electrocatalyst according to claim 2, characterized in that: The high temperature calcination temperature is 600-800°C.

4. The method for preparing the Co-NC electrocatalyst according to claim 3, characterized in that: The temperature of the high temperature calcination is 750°C.

5. The method for preparing the Co-NC electrocatalyst according to claim 2, characterized in that: The mass ratio of SBA-15 to cobalt nitrate is 1:3, and the amount of ethanol added is limited to 0.5 g SBA-15 corresponding to 30 mL ethanol.

6. The method for preparing the Co-NC electrocatalyst according to claim 2, characterized in that: The preparation method of SBA-15 comprises the following steps: Weigh 6.0g P123 and dissolve it in water. Use hydrochloric acid to adjust the pH of the solution. Keep it at 40℃ for 3h, then add TEOS, stir for 24h, and age it for 24h. After filtering, washing, and drying, calcine it in a muffle furnace at 550℃ for 8h to obtain the final sample SBA-15.

7. A use of the Co-NC electrocatalyst as claimed in claim 1, characterized in that: The Co-NC electrocatalyst is used as a trifunctional catalyst in electrochemical hydrogen evolution reaction HER, oxygen evolution reaction OER and oxygen reduction reaction ORR.

Citation Information

Patent Citations

  • Catalytic ozone water treatment method using cobalt-containing nitrogen-doped ordered mesoporous carbon as catalyst

    CN113336310A

  • Mesoporous nitrogen-doped carbon-loaded transition metal monatomic material as well as preparation method and application thereof

    CN113611883A